2021
DOI: 10.1097/jcma.0000000000000631
|View full text |Cite
|
Sign up to set email alerts
|

The risk of stroke after acute myocardial infarction in patients with and without atrial fibrillation: A nationwide cohort study

Abstract: Background: Acute myocardial infarction (AMI) and atrial fibrillation (AF) are risk factors for stroke. The risk of stroke after AMI may differ between patients with and without AF. The aim of this study was to evaluate the impact of AF on stroke in patients after the first AMI. Methods: This was a retrospective, nationwide cohort study. Patients with a primary diagnosis of a first AMI between 2000 and 2012 were included. All patients were followed up until ischemic stroke or transient ischemic attack (TIA), o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…In the setting of AMI, AF can manifest either as a pre-existing condition or as a complication. Previous studies indicate an incidence ranging from 2-21% for AF complicating AMI [19, 20]. Consistent with our results, studies also showed that patients with AF following AMI had a significantly higher long-term risk for fatal and non-fatal stroke compared to those without AF regardless of their age, gender or interventional treatment [20, 21].…”
Section: Discussionsupporting
confidence: 91%
“…In the setting of AMI, AF can manifest either as a pre-existing condition or as a complication. Previous studies indicate an incidence ranging from 2-21% for AF complicating AMI [19, 20]. Consistent with our results, studies also showed that patients with AF following AMI had a significantly higher long-term risk for fatal and non-fatal stroke compared to those without AF regardless of their age, gender or interventional treatment [20, 21].…”
Section: Discussionsupporting
confidence: 91%
“…This is believed to be a dangerous situation that may lead to death. [5][6][7] Swift detection and medical intervention are vital to restore blood flow and minimize damage. Troponin and creatine kinase are current biomarkers for AMI diagnosis, whereas percutaneous coronary intervention (PCI) is the common approach, alongside drug therapies.…”
Section: Introductionmentioning
confidence: 99%